Исследование мехатронной системы для автономного генерирования напряжения переменной частоты постоянной амплитуды на базе магнитоэлектрического генератора и полупроводникового преобразователя - Волков, А.Г.; Зиновьев, Г.С.; Харитонов, С.А. (Технічна електродинаміка, 2012)
Static electromagnetic processes in a mechatronic system for generating autonomous voltage consisting of a synchronous generator with permanent magnet and semiconductor converter, currentinverter, or AC-DC converter, perform the role of reactive load were investigated.Ratios for calculating the basic parameters of the converter, to assess the weight and size parameters of the systemare obtained.